Consumers' propensity to avoid seeking assistance: Conceptualization and scale development. (December 2022) - Sangle-Ferriere, Marion; Voyer, Benjamin G.
Consumers are increasingly confronted with complex processes and technologies as part of their daily consumption. This difficulty, in turn, can hinder their experience and may have negative consequences in terms of satisfaction, word of mouth, and repurchase behaviors. Although companies often offer customer assistance, many consumers do not make the step to ask for help. In this research, we introduce a social psychological framework centered around the threats associated with help-seeking to better explain help-avoidant behaviors. Doing so, we introduce and develop the "propensity to avoid seeking assistance" construct to better understand what triggers and hinders customers' assistance request behavior – or lack thereof. By offering and validating a new scale to measure such behavior, this research adds a methodological contribution to the literature. It also contributes to better explain the behavior of customers who would rather abandon using a product or service than ask for help.